Sexuality in Pediatric Spinal Cord Injury - Papadakis, Jaclyn Lennon (Top Spinal Cord Inj Rehabil, 2017)
Sexual development and sexuality in youth with pediatric spinal cord injury (SCI) are critical areas clinicians must be aware of and discuss when working with youth and their families. In addition to the general sexuality issues and challenges of adolescence and adult development, youth with SCI face unique physical and psychosocial issues. The goal of this article is to provide a developmentally based discussion of sexuality in individuals with SCI from infancy through emerging adulthood. An overview of psychosocial issues related to sexual development and sexuality are presented for each stage of sexual development along with recommendations for clinical practice, including patient and caregiver education and counseling. In order to establish expectations for youth with SCI, long-term outcomes related to sexuality and fertility of adults with pediatric-onset SCI are presented.